Managing Patient Falls in Psychiatric Inpatient Units: Part 1. Issue 1 (January 2016) - Abraham, Sam
Abstract : The problem addressed in the current quantitative, descriptive study was the significantly higher number of patient falls in hospital inpatient psychiatric units than in medical-surgical areas, resulting in patient-safety issues. The purpose of this study was to explore psychiatric unit directors' perceptions of the factors that contribute to patient falls in the State of Michigan. Two research questions guided the study: ( a ) What are psychiatric unit directors' perceptions of the possible intrinsic factors that contribute to patient falls in the psychiatric inpatient units, and ( b ) what are psychiatric unit directors' perceptions of the possible extrinsic factors that contribute to patient falls in the psychiatric inpatient units? An online survey was the tool used to gather data from the State of Michigan psychiatric unit directors. The analyses for the 2 questions indicated the participants believed that intrinsic factors were more strongly related to the likelihood of patient falls than were extrinsic factors.